Caracterización fisicoquímica de lodos PTAP y cenizas de lodos como posible uso en la industria de la construcción (2020)
In the following research work, the physicochemical characterization of sludge from the drinking water treatment plant, located in the city of Barranquilla, Colombia, was carried out; one sample was calcined at 800 ° C and the other part was exposed to the ambient for drying. The calcined and uncalcined muds were characterized by different techniques such as; scanning electronic microscopy (SEM), density, fineness, laser diffraction (DRL), x-ray diffraction (XRD); pozzolanic activity and X-ray fluorescence (XRF). In these results, it could be established that the samples of uncalcined mud could have a composition of O: 47.51%, Si: 28.79% and Al: 11.96%, while for calcined mud, percentages of O were found: 47.65%, Si: 28.51% and Al: 11.88%. The physical characterization shows average density values of 2.75 g / cm3 with a standard deviation of 0.06; for the uncalcined mud sample 2.76 g / cm3 for the calcined sample with a standard deviation of 0.04; Average fineness percentages between 54.8 to 56.5%. The results of laser ray diffraction show that 90% by volume of the analyzed particles show a smaller diameter of 571μm. The chemical characterization allowed establishing the percentages of the components present in each of these, obtaining values for the mud sample without calcine values of (Quartz: 34.3% Ilite: 29.4%, Kaolinite 1st 21.7%) and for the calcined mud sample (Quartz: 39.1% Ilite 2M1 46.1%). According to its characteristics and by the Chapelle method, the calcined sample is classified as pozzolan with values of 1837 mg CaOH2.